Professional Development to Support Students with Disabilities in Multi-Tier Classrooms: A Case Study - Blanks, Brooke (Journal of the American Academy of Special Education Professionals, 2013)
The purpose of this study was to understand general education teachers’ experiences with a school-wide effort to increase the use of evidence-based teaching practices that were highlighted through a professional development workshop in evidence-based reading instruction. A qualitative case study method was used to describe the experiences of five kindergarten and first grade teachers with a professional development program that was part of a school improvement initiative in early reading. Two themes emerged from the analysis of the data. Theme 1: Teachers do what they know how to do. Theme 2: Professional development must be evidence based. Implications of these findings for future practice and research are discussed.